NiSe2/Ni(OH)2 Heterojunction Composite through Epitaxial-like Strategy as High-Rate Battery-Type Electrode Material - Mei, Hao; Huang, Zhaodi; Xu, Ben; Xiao, Zhenyu; Mei, Yingjie; Zhang, Haobing; Zhang, Shiyu; Li, Dacheng; Kang, Wenpei; Sun, Dao Feng (Nano-Micro Letters, 2020)
Constructing heterojunction is a promising way to improve the charge transfer efficiency and can thus promote the electrochemical properties. Herein, a facile and effective epitaxial-like growth strategy is applied to NiSe2 nano-octahedra to fabricate the NiSe2-(100)/Ni(OH)2-(110) heterojunction. The heterojunction composite and Ni(OH)2 (performing high electrochemical activity) is ideal high-rate battery-type supercapacitor electrode. The NiSe2/Ni(OH)2 electrode exhibits a high specific capacity of 909 C g−1 at 1 A g−1 and 597 C g−1 at 20 A g−1. The assembled asymmetric supercapacitor composed of the NiSe2/Ni(OH)2 cathode and p-phenylenediamine-functional reduced graphene oxide anode achieves an ultrahigh specific capacity of 303 C g−1 at 1 A g−1 and a superior energy density of 76.1 Wh kg−1 at 906 W kg−1, as well as an outstanding cycling stability of 82% retention for 8000 cycles at 10 A g−1. To the best of our knowledge, this is the first example of NiSe2/Ni(OH)2 heterojunction exhibiting such remarkable supercapacitor performance. This work not only provides a promising candidate for next-generation energy storage device but also offers a possible universal strategy to fabricate metal selenides/metal hydroxides heterojunctions. Highlights: 1 A facile and effective epitaxial-like growth strategy is applied to fabricate the NiSe2/Ni(OH)2 heterojunction composite. 2 The assembled asymmetric supercapacitor based on the heterojunction composite surpasses most of the reported results. It is the first time that the powdered electrode materials can have such large capacity, high rate, and extreme long cycle life.